173 Identification of Biological Markers to Detect Early Estrus in Pre-Pubertal Gilts. (12th April 2022) - Dierking, Shannon L; Morton, Jodi; Pinilla, Juan Carlos; Gonda, Michael; Clapper, Jeffrey A; Levesque, Crystal L
Abstract: A proven predictor of reproductive success in swine breeding herds is age at puberty. Early puberty is associated with improved long-term reproductive performance. The objective of this study was to identify biomarkers of reproductive success at key periods in gilt reproductive development. Pre-pubertal gilts (n = 13) in 2 cohorts were followed from 70 d of age until first estrus or 213-215 d of age. Vaginal epithelia were collected using a swabbing technique at 5 key timepoints during reproductive development (70/77, 100/110, 130, 160 d of age, and first estrus or end of trial). Of the 13 gilts, 3 exhibited estrus early (d169 to 171), 2 were average (d 194 to 195), 2 were late (d 203 to 213), 3 were deemed anestrus and 2 had a silent estrus (one prior to d160 and 1 after d200). Total RNA were isolated and relative gene expression measured for RPLP0 (reference gene), TLR-4, TLR-5, IGF-1, ER-alpha and TAC-3 by quantitative real-time RT-PCR. Target genes were those involved with cellular protein function within the reproductive tract (IGF-1) and that prevent infection while allowing fertilization and implantation to occur (toll-like receptors 4 and 5). Gene ER-alpha is essential in the maturation of the female phenotype. Gene TAC-3 is critical for gonadal function. Comparison of relative expression of each gene of interest at different time points relative to 70 d was performed using the PCR package in RStudio (version 1.2.5025). Expression of IGF-1 and TAC-3 were up-regulated 9-fold and 7-fold, respectively, at the start of boar exposure (d 160; P < 0.05). Expression of ER-alpha tended to be upregulated 3-fold at 100 d of age ( P = 0.08). Expression of TLR-4 and TLR-5 was not detected for most samples until standing estrus. These transcripts may be putative biomarkers for early estrus detection.